The effects of a static exercise program verses Swiss ball training for core muscles of the lower back and pelvic region in patients with low back pain after child delivery. a single blind randomized control trial - Hadiqa Adnan; Misbah Ghous; Syed Shakil Ur Rehman; Irum Yaqoob (Journal of the Pakistan Medical Association, 2021)
Abstract Objectives: The objective of the study was to determine the effects of static exercise program verses Swiss ball training for core muscles of the lower back and pelvic region in patients with low back pain after child delivery. Methods: This was a prospective single blind randomized control trial conducted on a sample of 30 patients with low back pain from March 2018to December 2018. Patients were divided into 2 groups through seal envelop method i.e. static core exercises group (n=15) and Swiss ball training group (n=15). The outcome measures used for this study were numeric pain rating scale (NPRS), Oswestry disability index (ODI), goniometry and Core stability assessment scale. Data was analyzed by SPSS 21. Results: The mean age of patients in static core exercises group was 28.38 ± 4.8 years and mean age of Swiss Ball training group was 29.57 ± 3.3 years. Between group analysis showed non-significant difference whereas within group analysis showed significant improvement at post intervention. Conclusions: Both groups showed significant difference in reduction of pain (NPRS), in disability level due to LBP (ODI), better ROM flexion/extension of lumbar and achieving better strength at core stability assessment scale (CSA). These findings suggest that both exercise protocols are equally effective in rehabilitation of postpartum low back pain. Keywords: low back pain Postpartum Swiss ball training Static Continuous...